Pengolahan Limbah Sampah Domestik Menjadi Pupuk Kompos Skala Komunal Di Desa Sukunan - Dicky Aulia Rachman; Agus Riyadi (DPPM Universitas Pelita Bangsa, 2022)
The accumulation of garbage and indiscriminate disposal of waste in open areas will cause soil pollution which has an impact on groundwater channels. To reduce waste independently, Sukunan Hamlet carries out several processing processes including waste banks, household-scale composting and communal, glass waste treatment, styrofoam waste treatment, charcoal briquettes, plastic waste crafts, livestock manure biogas, communal scale wastewater treatment installations. This study aims to determine the process of processing domestic waste into compost in the village of Sukunan with the type of method used in this study, namely descriptive, by providing a clear description with the main focus being to reveal a problem and situation as it is the data collected consists of primary data and primary data. secondary. Waste management in Sukunan Village is well managed and structured, one of which is processing organic waste which is made into compost so that the waste can be useful for the surrounding community. Keywords: Garbage, Compost, Communal, Sukunan Village